Extension Strategies as Tools of Competitiveness for FPOs: An Analytical Study - Yadav, Hema; Paliwal, Manisha; Wadkar, Sagar (Journal of Agricultural Extension Management, 2024)
FPOs are farmers' collectives, with membership mainly comprising small/ marginal farmers (around 70 to 80%). As of now, more than 8700 FPOs have been registered under the Producers' Company & Cooperative Act, section 8 company act, society act, and trust act. The study uses literature review and follows a case-based approach to assess the elements of extension strategic interventions required to attain competitiveness and better business performance of FPOs. The study's objective is to understand how effective extension strategies lead to competitiveness with the help of the APP (Asset-Process-Performance) framework. This framework has been implemented to analyse Savitribai Phule Goat Farmer Producers Company Ltd. (SPGFPCL) based at Maharashtra. Focus group discussions with the leaders and members of the FPO reveal that this unique form of collective organization with a blend of deployment of extension strategies with good governance and professional management has paved the way towards business competitiveness